Integration of remote sensing-GIS Techniques for mapping Seagrass and Ocean Colour off Malaysian Coasts - Hashim, Mazlan; Abdullah, Adeli; Rasib, Abd Wahid (Asian Association on Remote Sesning, 1997)
This paper describes seagrass and ocean colour mapping off Peninsular Malaysia. The seagrass were extracted form visible bands of Landsat TM using the depth invariant index of the seabottom type. The ocean colour which is much referred to micro-plankton concentration is derived by regressing samples form known site collected at time of satellite overpass. Both these information were then input into GIS database which were also being established to assist the Marine Fisheries Management and Development Center in managing and monitoring coastal areas.